Insights into neuromyelitis optica spectrum disorder and pregnancy from a single-center study in Thailand - Nuttakarn Budtarad; Tatchaporn Ongphichetmehta; Sasitorn Siritho (Scientific Reports)
Abstract Our study focused on assessing disease and pregnancy outcomes in Thai patients with Neuromyelitis Optica Spectrum Disorder (NMOSD), a condition that disproportionately affects women of childbearing age and poses risks to both mother and fetus. We retrospectively analyzed eight NMOSD patients with a total of 10 pregnancies from our central nervous system inflammatory demyelinating diseases (CNS-IDDs) registry. Over a 12-months spanning from before pregnancy to 12 months postpartum, we observed 13 relapses, with a notable 76.92% occurring postpartum. The mean annualized relapse rate (ARR) peaked at 1.2 (SD ± 1.93) during specific postpartum intervals (0–3 and 6–9 months postpartum), significantly increasing from 0.20 (SD ± 0.42) in the 12 months before pregnancy (BP) to 1.00 (SD ± 1.49) during the 12 months postpartum (PP). Disability, assessed using the Expanded Disability Status Scale (EDSS) scores, worsened from 1.56 (SD ± 2.18) before pregnancy to 2.1 (SD ± 2.63) at six months postpartum. Maternal and fetal complications were prevalent, with six out of nine pregnancies experiencing adverse outcomes such as false labor, premature rupture of membranes, postpartum hemorrhage, intrauterine growth restriction, preterm birth, stillbirth, and low birth weight. Based on our findings, azathioprine and rituximab may be suitable treatment options for maintaining therapy throughout pregnancy, particularly in cases of high disease activity. Our study highlights the critical need for comprehensive management strategies for NMOSD patients of childbearing age. Preconception planning and counselling, along with early obstetrical consultation and closely monitored treatments during pregnancy and postpartum, are vital to mitigating pregnancy-related relapses and adverse fetal outcomes in this vulnerable patient population.